2021
DOI: 10.37150/jl.v4i1.1395
|View full text |Cite
|
Sign up to set email alerts
|

Aplikasi Terapi Murottal Al-Quran Terhadap Tekanan Darah Pada Penderita Hipertensi Di Wilayah Kerja Puskesmas Nagrak Cianjur

Abstract: Hypertension is an increase in systolic blood pressure of at least 140 mmHg or diastolic pressure of at least 90 mmHg. Hypertension is the main risk factor that can lead to heart disease, congestive heart failure, stroke, visual impairment and kidney disease. Murottal Al-Quran therapy is a therapy that can accelerate the reduction of blood pressure in patients with hypertension. Objective: To find out the effect of Al-Quran murottal therapy on blood pressure in patients with hypertension in the working area of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
0
0
1
Order By: Relevance
“…Listening to the Al-Quran will provide peace in Al-Quran is a non-pharmacological treatment by relieving stress, increasing happiness in life, decreasing levels of depression, anxiety, and sadness ending with peace of mind so that it can overcome various kinds of diseases. (Apriliani, Basri and Mulyadi, 2021). Research resultUmam et al ( 2023)showed that Al-Quran murottal therapy can reduce blood pressure in 2 hypertensive patients at Jendral Ahmad Yani Metro Regional General Hospital.…”
Section: Resultsmentioning
confidence: 99%
“…Listening to the Al-Quran will provide peace in Al-Quran is a non-pharmacological treatment by relieving stress, increasing happiness in life, decreasing levels of depression, anxiety, and sadness ending with peace of mind so that it can overcome various kinds of diseases. (Apriliani, Basri and Mulyadi, 2021). Research resultUmam et al ( 2023)showed that Al-Quran murottal therapy can reduce blood pressure in 2 hypertensive patients at Jendral Ahmad Yani Metro Regional General Hospital.…”
Section: Resultsmentioning
confidence: 99%
“…Selain itu, untuk mendukung efektivitas penurunan nyeri yang dirasakan pasien, diberikan pula terapi murotal Al-Quran. Terapi murotal Al-Quran ini bertujuan untuk mengurangi rasa nyeri dan pasien merasa rileks dan nyaman 14 .…”
Section: Intervensi Keperawatanunclassified
“…Terapi murotal terhadap pembacaan Al-quran diwujudkan dengan perubahan arus listrik pada otot, perubahan sirkulasi darah, perubahan detak jantung, dan perubahan konsentrasi darah di kulit (Aini et al, 2017). Perubahan ini menunjukkan nada refleks yang rileks atau menurun, yang menyebabkan arteri menjadi rileks, kadar darah di kulit meningkat, dan detak jantung melambat (Irawati & Lestari, 2017).…”
Section: Pendahuluanunclassified
“…Peneliti menggunakan audio mulottar surat Ar-Rahman sebagai alat relaksasi bagi pasien hipertensi (Hartiningsih et al, 2022). Terapi dimainkan kepada pasien, dan efek suara audio dikaitkan dengan proses transmisi impuls suara ke dalam tubuh dan pengaruhnya terhadap sel (Apriliani et al, 2021). Bunyi yang ditangkap oleh telinga diterima oleh sistem saraf pusat dan diteruskan ke seluruh bagian tubuh.…”
Section: Pembahasan Pengaruh Terapi Murotal Terhadap Penurunan Tekana...unclassified